1992
DOI: 10.1111/j.1600-0447.1992.tb10326.x
|View full text |Cite
|
Sign up to set email alerts
|

The interrater reliability of a Dutch version of the Structured Clinical Interview for DSM‐III‐R Personality Disorders

Abstract: This study presents data on the interrater reliability of a Dutch version of the Structured Clinical Interview for DSM-III-R Personality Disorders (SCID-II). Seventy outpatients were interviewed before the start of their treatment by one rater, while a second rater observed. Both raters were instructed to make independent ratings and the second rater was not allowed to participate in the discussion. On criterion level, interrater reliabilities appear to be very good, with a few exceptions (most reliabilities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
2
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 13 publications
1
35
2
2
Order By: Relevance
“…κ values based on categorical diagnoses in the present study were lower than those reported in a study of treatment-seeking patients [26], which may be a function of the samples used in each study. The base rate for PDs is higher in patient populations, so more variability in pathologic personality symptoms was probably found in the sample of Arntz et al [26].…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…κ values based on categorical diagnoses in the present study were lower than those reported in a study of treatment-seeking patients [26], which may be a function of the samples used in each study. The base rate for PDs is higher in patient populations, so more variability in pathologic personality symptoms was probably found in the sample of Arntz et al [26].…”
Section: Discussioncontrasting
confidence: 95%
“…κ values based on categorical diagnoses in the present study were lower than those reported in a study of treatment-seeking patients [26], which may be a function of the samples used in each study. The base rate for PDs is higher in patient populations, so more variability in pathologic personality symptoms was probably found in the sample of Arntz et al [26]. Researchers have described this issue as the "base rate problem" of κ: "Kappa is influenced by the illness base rate, such that a few diagnostic disagreements have a more pronounced effect on reliability when the base rate is either very low or high" ( [13], p 226).…”
Section: Discussioncontrasting
confidence: 95%
“…The inter-rater reliability ranged from 0.77 for the obsessive-compulsive PD to 0.82 for the avoidant PD. The overall Kappa was 0.80 [27] . These figures are comparable to the associations obtained in the study of Masthoff and Trompenaars, who found an overall Kappa of 0.87 for two well-trained and certified raters in a large sample of psychiatric outpatients [28] .…”
Section: Scid-iimentioning
confidence: 82%
“…O'Boyle and Self, 1990;Skodol et al, 1991;Arntz et al, 1992b;Renneberg et al, 1992;First et al, 1995b;Dreessen and Arntz, 1998b;Arntz, 1999).…”
Section: Structured Clinical Interview For Dsm-iii-r Personality Disomentioning
confidence: 96%
“…All of them were experienced in diagnosing and treating psychotherapy patients and practised as therapists in the`Academic Section Behavior Therapy'. Five of them (AA, LD, MvR, WK, HvG) had participated in our SCID-II reliability studies which demonstrated good interrater reliabilities (Arntz et al, 1992b;Dreessen and Arntz, 1998b). The other five interviewers were trained extensively by doing joint interviews with several experienced interviewers who participated in our reliability studies.…”
Section: Scid-ii Interviewersmentioning
confidence: 99%